Determining performance differences between bidders that acquire listed targets and non-listed targets in Bursa Malaysia / Mariathy Karim, Saiful Hafizah Jaaman and Azlida Muhamad - Karim, Mariathy; Jaaman, Saiful Hafizah; Muhamad, Azlida (Universiti Teknologi MARA Cawangan Pahang, 2009)
The purpose of this paper is to measure the relative performance between bidders that acquire listed targets and non-listed targets in Bursa Malaysia. The performance is evaluated by using Sharpe performance measure for the year 1995 until 2003 which consists of 870 bidders with its targets on the announced date. The finding shows that the performances of bidders that acquire non-listed target in Bursa Malaysia are better than the performance of bidders that acquire listed target in Bursa Malaysia. The involvements of risk are also considered in this study. Excel software is used to estimate the parameters and to analyse the performance values.